2021
DOI: 10.52131/jom.2021.0303.0057
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Green Servant Leadership on Organizational Sustainability: The Mediating Role of Green Human Resource Management Practices

Abstract: Green human resource management practices in the presence of green servant leadership have become a prime business concern for sustainable growth. This study examines the mediating role of green HRM practices between green Servant leadership and sustainable firm performance, particularly in the manufacturing sector. Cross-sectional data were collected from 480 owners/human resource managers working in the manufacturing industry in Pakistan using a convenient sampling technique. A partial least squares approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Several study findings show that GHRM practices affect green creativity (Muisyo et al,2022Alyahya, 2023Abualigah et al, 2022). Previous research has shown that GHRM plays an important role in mediating green transformational leadership relationships (Sun et al, 2022;Singh et al, 2020;Jia et al, 2018) green servant leadershipI (Sher and Nawaz, 2021;Alyahya et al, 2023;Darvishmotevali et al, 2021). Therefore, we recommend that:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several study findings show that GHRM practices affect green creativity (Muisyo et al,2022Alyahya, 2023Abualigah et al, 2022). Previous research has shown that GHRM plays an important role in mediating green transformational leadership relationships (Sun et al, 2022;Singh et al, 2020;Jia et al, 2018) green servant leadershipI (Sher and Nawaz, 2021;Alyahya et al, 2023;Darvishmotevali et al, 2021). Therefore, we recommend that:…”
Section: Literature Reviewmentioning
confidence: 99%